Different functions of PHF10 isoforms – subunits of the PBAF chromatin remodeling complex - A. A. Sheynov; V. V. Tatarskiy; A. M. Azieva; S. G. Georgieva; N. V. Soshnikova (Вавиловский журнал генетики и селекции)
Chromatin remodelling multiprotein complexes play an important role in regulation of gene expression in embryogenesis and in the adult organism. Mutations in the subunits of the complexes are often lethal or lead to developmental defects. Complexes consist of core subunits and a specific module. The core consists of ATPase and structure subunits, specific subunits of the module are necessary for chromatin binding. PHF10 (PHD finger protein 10) is a subunit of the PBAF (polybromo-associated BAF) chromatin remodelling complex subfamily. Conserved and highly regulated PHF10 is ubiquitously expressed in mammals as four different isoforms. The isoforms of PHF10 differ by domain structures and posttranslational modifications. All isoforms are highly regulated and included in the PBAF complex in a mutually exclusive manner. Two of the PHF10 isoforms (PHF10-P) are expressed at a high level in neuronal and myeloid progenitors and are necessary for cell proliferation. These isoforms contain PHD (plant homeodomain) fingers for nucleosome binding and recruit RNA polymerase II on the promoters of cell cycle genes. Two other isoforms (PHF10-S) instead of PHD have PDSM (phosphorylation-dependent sumoylation motif), the motif for SUMO1 conjugation. PHF10 is the most unstable subunit of the PBAF complex. Stability can alter the turnover rate of the subunits of the PBAF complex. All PHF10 isoforms are degraded by β-TrCP ubiquitin ligase but PHF10-S isoforms contain a cluster of serins (X-cluster) for multiple phosphorylation by casein kinase I. This phosphorylation protects the β-TrCP degron from β-TrCP recognition and subsequently stabilizes the PHF10-S isoforms. Thus, the incorporation of PHF10 isoforms with different phosphorylation patterns and different stability into the PBAF complexes alters the functions of the entire PBAF complex and determines the range of genes undergoing remodelling.